Rhythms of Nature and Culture in the Art of M. K. Ciurlionis - Mond-Kozłowska, Wiesna (Respectus Philologicus, 2012)
This article aims to grasp the ontological constitutional principle known as correspondances des artes. The affinity of arts is usually interpreted as a functional quality, while the author holds that it is of ontic character as well. This results from the shared ontological reference of all natural phenomena of human life and, consequently, human creative work. Experimental knowledge of this metaphysical truth, according to the composer-synaesthetic Olivier Messiaen, is within the reach of very few people, even less so amongst the artists themselves. Mikalojus Konstantinas Čiurlionis, the Lithuanian composer and painter, was one of those very few. The main argument of the article, which is developed in the realm of the ontology of a piece of art, is the premise that the rhythm factor can serve as grounds for discussion to investigate the nature of the correspondances des artes. This was also the subject matter of the French phenomenologist Mikel Dufrenne’s writings (Dufrenne 1992, pp. 323–324). In addition, the author argues that all so-called organic aesthetics (Tatarkiewicz 1985, p. 84), those who claim that the laws of the creative process depend on the laws of nature, prove the existence of the common and shared ontic base of the world, logos. This base belongs to both natural and created ontological phenomena. The synaesthetic pictorial and musical oeuvre of Čiurlionis is the research field for inferring the initial argument of the paper.